Green marketing education and strategy to increase circular economy adoption in Sidomukti Village community, Lamongan Regency - Muhammad Sulton; Ika Purwanti; M. Ainul Mahbubillah; Hadad Alwi; Abdul Rozaq Alfarisi (Journal of Community Service and Empowerment, 2025)
The Community Partnership Program (PKM) implemented in Sidomukti Village, Lamongan Regency, focuses on education and green marketing strategies to increase the adoption of a circular economy. The program objectives are: Empowering communities through processing coconut water waste into nata de coco. The activity is carried out by providing training on product marketing strategies, which are expected to improve the economic welfare of the community and reduce waste by encouraging local entrepreneurship. Despite challenges such as limited knowledge and facilities, ongoing training and support are expected to help communities overcome obstacles and achieve success. The benefits of the program include: Improving production infrastructure and utilizing digital marketing. The method used is to build sustainable partnerships and conduct periodic evaluations. This method is expected to provide long-term benefits for the people of Sidomukti Village. The program activities include socialization, training, technology application, mentoring, and evaluation. The community learns the production and marketing process of nata de coco, which has high economic value. As a result, the community gains new skills, increases income, and awareness of sustainable waste management. This program encourages collaboration with academics, government, and the private sector for better business development. It is that this program will succeed in improving community and environmental welfare. It is recommended to continue training and product innovation, was designed in the form of the enrichment program for weekend class was effectively run.